Genetic diversity of Plasmodium falciparum parasites from Kenya is not affected by antifolate drug selection - Nzila, A.M; Mberu, E.K; Nduati, E; Ross, A; Watkins, W.M; Sibley, C.H (International journal for parasitology, 2002)
The genotypes of merozoite surface protein-1, merozoite surface protein-2 and glutamine rich protein are frequently used to distinguish recrudescence from reinfection when parasitaemia reappears after antimalarial drug treatment. However, none of the previous reports has clearly assessed the change of genetic diversity following drug treatment. In the present study, we have assessed the impact of pyrimethamine/sulfadoxine and chlorproguanil/dapsone on the genetic diversity of isolates and the multiplicity of infection in patient isolates from Kilifi, Kenya. We have analysed the length polymorphism of merozoite surface protein-1, merozoite surface protein-2 and glutamine rich protein and the data clearly show that treatment with pyrimethamine/sulfadoxine and chlorproguanil/dapsone did not change the multiplicity of infection found in patients, in contrast to the selection that these drugs exert on the genes encoded by the target enzymes. In addition, we report that children of less than 2 years tend to have fewer numbers of clones per isolate when compared with older children. Overall, this study shows that the selection for genes that confer drug resistance is not a factor in reducing the genetic diversity of parasite clones in a patient.